2011
DOI: 10.1371/journal.pntd.0000944
|View full text |Cite
|
Sign up to set email alerts
|

Ruminant Brucellosis in the Kafr El Sheikh Governorate of the Nile Delta, Egypt: Prevalence of a Neglected Zoonosis

Abstract: BackgroundBrucellosis is a neglected tropical zoonosis allegedly reemerging in Middle Eastern countries. Infected ruminants are the primary source of human infection; consequently, estimates of the frequency of ruminant brucellosis are useful elements for building effective control strategies. Unfortunately, these estimates are lacking in most Middle East countries including Egypt. Our objectives are to estimate the frequency of ruminant brucellosis and to describe its spatial distribution in Kafr El Sheikh Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
61
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 24 publications
6
61
1
Order By: Relevance
“…Seroprevalence studies conducted throughout the developing world demonstrate that when one looks, Brucella infection is frequently found among sampled livestock populations [1115,16 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…Seroprevalence studies conducted throughout the developing world demonstrate that when one looks, Brucella infection is frequently found among sampled livestock populations [1115,16 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosisis considered aneglected zoonosis by the world health organization and has been identified as having the highest public health burden across all sections of the community [9]. In human, Brucellosis is always caused by B. melitensis (cause Undulant or Malta fever) followed by B. suis, B. abortus and B. canis [10].…”
mentioning
confidence: 99%
“…However, results from other regional or subregional studies indicated that the seroprevalence of brucellosis in cattle and buffalo was ranged from about 3% to 17% (Samaha et al., ; Hegazy et al., ; Holt et al., ; Mahboub et al., ). The proportion of seropositive sheep was around 2% except in 2009 (3.7%), which is quite lower than findings by other regional studies (3% to 26%) (Samaha et al., ; Hegazy et al., ; Holt et al., ; Mahboub et al., ). However, poor implementation of random sampling strategies increases the unreliability of the outcomes (Hegazy et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that farmers would be satisfied with the level of compensation as it represents <50% of the market value. This could be one of the main factors hindering the success of the control programme (Hegazy et al., , ; Holt et al., ). Farmers may be more willing to comply with serological testing requirements if compensation was given at the market value of the positive animals and the process of compensation was easier and faster than it is currently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation